1983
DOI: 10.1111/1523-1747.ep12537474
|View full text |Cite
|
Sign up to set email alerts
|

Complement-Activating Immune Deposits in Systemic Lupus Erythematosus Skin

Abstract: Immune deposits at the cutaneous basement membrane zone are a characteristic feature of systemic lupus erythematosus. Previous studies using immunofluorescent methods to detect complement components have provided evidence that some deposits contain immune complexes capable of activating complement. However, this important biologic property of complexes has not been detected or measured using functional assays, and it has not been determined whether immune deposits can activate complement at the basement membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There was a positive result in 42%-100% lesion cases, and 32%-92.9% in non-lesion cases. 7,16,[20][21][22][23][24][25][26][27][28] The pattern of immunodeposition at the DEJ was homogenous, thready, strippled, granular, and linear. A homogenous pattern was defined as a thick, solid, well-demarcated, continued line at the DEJ.…”
Section: Dif Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a positive result in 42%-100% lesion cases, and 32%-92.9% in non-lesion cases. 7,16,[20][21][22][23][24][25][26][27][28] The pattern of immunodeposition at the DEJ was homogenous, thready, strippled, granular, and linear. A homogenous pattern was defined as a thick, solid, well-demarcated, continued line at the DEJ.…”
Section: Dif Testsmentioning
confidence: 99%
“…The common pattern and immunodeposits at the DEJ were granular and IgM, respectively. 20,23,29 DIF tests of LE-specific skin lesions (Table 1)…”
Section: Dif Testsmentioning
confidence: 99%
“…Complements are activated in many skin diseases, so complement deposition can be seen in some inflammatory skin diseases, such as lichen planus, lupus and even atopic dermatitis . In addition, a previous report showed that the C3b degradation product C3d was observed at the dermal‐epidermal junction even in normal human skin .…”
Section: Evidence Of Non‐complement Relevancementioning
confidence: 99%